2020
DOI: 10.1111/oik.07378
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between individual metabolic rate and patch departure behaviour: evidence from aquatic gastropods

Abstract: Individual energy requirements are tightly related to individual resource use and by extension of space‐use patterns and other traits at higher levels of the ecological hierarchy. However, there is still little experimental evidence linking individual energetics and space‐use behaviour. Individual energy requirements scale mainly with body size and temperature, but these do not explain all individual variation. Therefore, studies focused on inter individual variation in resource and space use behaviour can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 104 publications
(173 reference statements)
2
10
0
Order By: Relevance
“…Thus, larger individuals gave up the resource patch earlier and travelled further in search of food than smaller ones. Similarly, recent studies have observed the negative size dependency of giving‐up time among several Gastropod species (Cozzoli et al., 2018, 2020).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Thus, larger individuals gave up the resource patch earlier and travelled further in search of food than smaller ones. Similarly, recent studies have observed the negative size dependency of giving‐up time among several Gastropod species (Cozzoli et al., 2018, 2020).…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, recent studies have observed the negative size dependency of giving-up time among several Gastropod species (Cozzoli et al, 2018(Cozzoli et al, , 2020. (Gillooly et al, 2001;West et al, 1997).…”
Section: Case Studymentioning
confidence: 54%
See 1 more Smart Citation
“…For reasons that are still not completely understood, the metabolic scaling slope of benthic macroinvertebrates often shows less steep slopes (i.e., ~0.30 to ~0.55) than the −0.75 value. Whether this variation in macroinvertebrate metabolic scaling slope is related to environmental factors, such as water temperature [58,59] and biological factors, such as predation pressure [60,61], is less known. Moreover, this variation of metabolic responses in relation to predation threats may be temperature-dependent [62,63].…”
Section: Patterns Of Lsdr Molo and Lsdr Pont (All Months Included)mentioning
confidence: 99%
“…Animals determine behaviors regarding their physiological needs and reproductive goals (Cozzoli et al, 2018(Cozzoli et al, , 2020Prato et al, 2006;Shokri et al, 2019Shokri et al, , 2021Shuhaimi & Pascoe, 2001), once they reach sexual maturity, new dimensions would be added to their internal state and hence, the organism foraging decisions (Becker et al, 2012;Cruz-Rivera et al, 2017;Mowrey & Portman, 2012;Ward, 1985Ward, , 1986. Sex-related differences were shown in G. aequicauda during its feeding as a grazer on two green algae species (Cruz-Rivera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%